Nanoparticle-Based Drug Delivery Systems for Inflammatory Bowel Disease Treatment - Gao J; Li J; Luo Z; Wang H; Ma Z (Dove Medical Press, 2024)
Jian Gao,1 Jiannan Li,2 Zengyou Luo,1 Hongyong Wang,3 Zhiming Ma1 1Department of Gastrointestinal Nutrition and Hernia Surgery, The Second Hospital of Jilin University, Changchun, People's Republic of China; 2Department of Colorectal and Anal Surgery, The Second Hospital of Jilin University, Changchun, People's Republic of China; 3Department of Radiotherapy, The Second Hospital of Jilin University, Changchun, People's Republic of ChinaCorrespondence: Zhiming Ma, Department of Gastrointestinal Nutrition and Hernia Surgery, The Second Hospital of Jilin University, Changchun, People's Republic of China, Email mazhiming@jlu.edu.cnAbstract: Inflammatory bowel disease (IBD) is a chronic, non-specific inflammatory condition characterized by recurring inflammation of the intestinal mucosa. However, the existing IBD treatments are ineffective and have serious side effects. The etiology of IBD is multifactorial and encompasses immune, genetic, environmental, dietary, and microbial factors. The nanoparticles (NPs) developed based on specific targeting methodologies exhibit great potential as nanotechnology advances. Nanoparticles are defined as particles between 1 and 100 nm in size. Depending on their size and surface functionality, NPs exhibit different properties. A variety of nanoparticle types have been employed as drug carriers for the treatment of inflammatory bowel disease (IBD), with encouraging outcomes observed in experimental models. They increase the bioavailability of drugs and enable targeted drug delivery, promoting localized treatment and thus enhancing efficacy. Nevertheless, numerous challenges persist in the translation from nanomedicine to clinical application, including enhanced formulations and preparation techniques, enhanced drug safety profiles, and so forth. In the future, it will be necessary for scientists and clinicians to collaborate in order to study disease mechanisms, develop new drug delivery strategies, and screen new nanomedicines. Nevertheless, numerous challenges persist in the translation from nanomedicine to clinical application, including enhanced formulations and preparation techniques, enhanced drug safety profiles, and so forth. In the future, it will be necessary for scientists and clinicians to collaborate in order to study disease mechanisms, develop new drug delivery strategies, and screen new nanomedicines.Keywords: nanoparticles, inflammatory bowel diseases, targeted delivery, passive targeting, active targeting, drug delivery system